2014
DOI: 10.1088/2041-8205/798/1/l20
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Physical Model for the Gas Distribution in Galaxy Clusters

Abstract: The dominant baryonic component of galaxy clusters is hot gas whose distribution is commonly probed through X-ray emission arising from thermal bremsstrahlung. The density profile thus obtained has been traditionally modeled with a β-profile, a simple function with only three parameters. However, this model is known to be insufficient for characterizing the range of cluster gas distributions, and attempts to rectify this shortcoming typically introduce additional parameters to increase the fitting flexibility.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Note that Tomooka et al (2020) also measured a sharp radial transition at the edge of galaxy clusters in the line-of-sight velocity dispersion of tracer galaxies around RM clusters in the SDSS spectroscopic survey. Also note that splashback-like features in individual clusters were discussed in previous studies (Rines et al 2013;Patej & Loeb 2015;Tully 2015).…”
Section: Introductionmentioning
confidence: 53%
“…Note that Tomooka et al (2020) also measured a sharp radial transition at the edge of galaxy clusters in the line-of-sight velocity dispersion of tracer galaxies around RM clusters in the SDSS spectroscopic survey. Also note that splashback-like features in individual clusters were discussed in previous studies (Rines et al 2013;Patej & Loeb 2015;Tully 2015).…”
Section: Introductionmentioning
confidence: 53%
“…In cross-correlation the combinations X-ray and tSZ observations have yielded stacked gas density profiles that go beyond R 500 (e.g., Planck Collaboration et al 2013a; Eckert et al 2012), for a sub-set of massive clusters. Beyond R 500 there are theoretical gas density profiles from analytic calculations (e.g., Komatsu & Seljak 2001;Ostriker et al 2005;Patej & Loeb 2015) and predictions from numerical simulations (e.g., Roncarelli et al 2006;Nagai et al 2007;Vazza et al 2010;Pike et al 2014), with some of simulations provided a fitting function to their results. Like most halo profiles simulations show that the gas density profile is close to self-similar, but recently it was shown that at large radii self-similarity is broken by the mass accretion history of the halo (Lau et al 2015).…”
Section: Agn Feedbackmentioning
confidence: 99%
“…Meanwhile, the gas density profile ρ gas (r) is described with the model proposed by Patej & Loeb (2015) ρ gas (r) = Γf gas r r shock…”
Section: Spatial Distributions Of Gas Mass and Total Gravitational Massmentioning
confidence: 99%